Pengembangan Teknologi E-Marketplace Untuk Analisis Usaha Peternak Ayam Lokal di Kotawaringin Timur - Ahmad fahrudin Ansari; Nurahman Nurahman (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
East Kotawaringin Regency is one of the regencies in Central Kalimantan Province, Indonesia. The problems faced today are the marketing of local chicken livestock, the lack of information on local chicken farms and discussion media among breeders in the district and the management of transactions and reports that still use manual and even traditional recording which results in frequent loss of data. So, how to create an information system that can make it easier for customers to place orders via the Website without coming directly to the market and manage transaction data and reports in a systemized manner. To solve this problem, we need a Web-based E-Matketplace. To create this web-based E-Matketplace, we need an editor software for Macromedia Dreamweaver CS4 programming language, PHP programming language, and MySql database